Tipologi Penggunaan Hukum Tata Negara Darurat: Sebuat Studi Literatur - Ayuni, Qurrata (Jurnal Hukum & Pembangunan, 2022)
This paper discusses a number of categorizations of countries in dealing with emergencies. The development of studies on this typology is classified after a comparison of the approaches of countries analyzed by a number of experts. There are at least nine models used in this paper, namely; Roman Dictatorship Model, Neo Roman Model, Constitutional Emergency Powers, Statutory Authorization, Extra-Legal Action, The Executive Dictatorship, The Legislative Dictatorship, and The War Government. Some of these types have similarities and intersections in their use. Understanding the birth of this typology will enrich alternatives in dealing with emergencies more effectively and proportionally.